Hubungan Terpaan Iklan Pada Akun Instagram @sociolla dan Terpaan Online Customer Review Pada Sociolla Connect dengan Keputusan Pembelian Produk Kecantikan di Sociolla - Farasila, Iraisa; Pradekso, Tandiyo (Interaksi Online, 2020)
This research aims to find out the relationship between each variable, instagram ads (X1), and online customer review (X2) with beauty product purchasing decisions in Sociolla (Y). In this study use quantitative research methods. Sampling technique using non probability sampling with a total of 55 respondents. The analysis used to test the hypothesis is Kendall's Tau B test. The results showed that there is a positive relationship between instagram ads and the decision to purchase beauty products in Sociolla so that the theory used, namely Strong Advertising Theory, can be applied to this study. In addition, the results of the study also showed there is a positive relationship between online customer review and beauty product purchasing decisions in Sociolla so that the theory used, namely Cognitive Response Theory, can be applied to this study.